Crowdfunding Coordinated Money Waqf Savings as Alternative to Sharia Cooperative Financing - Muh. Abdulloh Hafith; Abu Azam Al Hadi; Ah. Ali Arifin (Budapest International Research and Critics University, 2021)
Cash waqf is waqf carried out by a person, group, institution or legal entity in the form of money, including in the sense of money is securities, such as shares and checks. The application of cash waqf today has greater advantages than traditional waqf, namely physical objects that do not move. The study aims to answer the question How to explore the potential of cash waqf by crowdfunding coordinated waqf savings and their management so that they become productive as an alternative to financing in sharia cooperatives. The method used is descriptive analytical by using two approaches, namely Sociological and case studies. Data collection techniques used are observation, interviews and documentation. The results of this research with a qualitative descriptive approach indicate that the excavation of cash waqf funds with the coordinated crowdfunding system of cash waqf savings is very effective and to maintain its sustainability, cash waqf must be managed productively by investing in Sharia business sectors with low risk.